Editorial: Methods papers. (2nd January 2019) - Gardiner, Elizabeth
Abstract: The utility of a methods section of a research paper is often tempered by the brevity demanded by manuscript word limitations. Whilst word limits help streamline a paper, a Methods section often bears the brunt of the editorial scalpel, resulting in only brief sketches of experimental protocols and consignment of methodology to online supplementary information files. To retain a place for important detailed methodology, and to encapsulate and highlight new and existing important techniques for platelet and megakaryocyte biology, the Platelets Journal Editorial board now accept Methods manuscripts.